DEVELOPING INSTRUCTIONAL MATERIALS BASED ON INQUIRY LEARNING MODEL - Sari, Nur Fadila; Ahmad, Djuwairiah; Nurpahmi, Sitti (English Language Teaching for EFL Learners Journal, 2020)
This research is aimed to developing instructional English materials for the students of the seventh grade especially in basic competencies 3.1, 4.1, 3.2, and 4.2 at MTs Madani Pao-pao based on 2013 curriculum supported by using inquiry learning model and using the concept of HOTS in indicators achieved. The research design used in this study was Research and Development (R&D). The development model used was ADDIE model. It consists of need analysis, design, development, implementation, and evaluation. The procedures included analyzing materials needed by spreading questionnaire to the students and analyzing the basic competencies used, designing a blueprint of materials and the instructional materials, and validating the material by the expert. There were 146 students as the respondents of 26 questionnaire questions. The instruments used in this research were the documents, questionnaire, and validation checklist. In this research, the expert was involved in order to validate the product. There were three systematic aspects that they validated of the product: Materials Systematic Organization, Systematic English Teaching and Systematic Content of English. Therefore, the result indicated that based on experts judgment as well as product development result, the developed basic competency 3.1 & 4.1 and basic competency 3.2 & 4.2 were applicable to be taught at the seventh grade students of Junior High School as topic in English for them.